Clinical characteristics related to long-term survival in durable responders with human epidermal growth factor receptor-type 2 metastatic breast cancer: a systematic review - Mansani, Fabio Postiglione; Ribas, Luiz Roberto Cavassola; Barbosa, Gabriel Weslwy; Machinski, Elcio; Matera, Maysa Ortolani (Mastology, 2026)
Objective: The aim of this study was to identify the characteristics of durable responders and compare them with other metastatic breast cancer profiles. Methods: This was a systematic literature review using databases such as PubMed, Embase, and Web of Science, in which 12 articles were selected for analysis. This study analyzed 9,474 patients, of whom 2,213 had a survival of 3–10 years (long survival) and 7,261 had a poor prognosis. Results: Among the survivors, 28.39% had de novo metastasis at diagnosis, in contrast to 71.6% in the group with the worst prognosis. Visceral metastases were more common in the control group (48.76%) and in the survivor group (46.05%), while nodal metastases were more prevalent in the survivor group (13.25%) and in the control group (11.60%). Single metastases were more prevalent in the survivors (61.81%) than in the controls (51.94%). Tumor resection was performed in 42.31% of survivors, compared to 14.90% in the group with the worst prognosis. Conclusion: It is concluded that patients with long-surviving HER2-positive metastatic breast cancer have distinct clinical characteristics, such as a lower incidence of multiple metastases and a higher prevalence of nodal metastases, as well as better outcomes related to primary tumor surgery